NEW LABOUR 'ETHICAL' FOREIGN POLICY - N. A. Stepanova (Vestnik MGIMO-Universiteta)
The article discusses problems and contradictions associated with the attempt of the Labour Party under the leadership of Tony Blair to start a 'new era' in international relations by putting the 'ethical dimension' into the heart of their foreign policy. Indeed, having come to power and possessing great credibility among the British society, New Labour undertook a number of actions, which marked the formal break with the practices of the previous governments. Thus, they shifted the focus from the foreign trade interests to human rights considerations on the international arena, introduced innovations in the field of international aid and development of poor countries, declared the priority of so-called 'advanced' national interests. These solutions, however, have led to some ambiguous results. The author argues that, on the one hand, the Labour Party 'new' foreign policy was a tribute to the historical tradition and continuity and on the other - the spirit of the times, as other Western countries leaders claimed similar statements, and that, in fact, it contributed to the moral authority of the government in the eyes of the British society. The article contains examples proving how ambiguity and contradictoriness of certain decisions have been the conscious choice made by politicians, when declared altruistic goals actually proved to protect interests of certain business structures and direct opposite of the stated ethical principles. It is suggested that the divergence between word and deed had been initially present in the New Labour international doctrine and that the 'ethical foreign policy' can be considered as one of the tools of Realpolitik. The author concentrates on such aspects of the New Labour foreign policy as development, aid, debt relief, and arms trade, rather than on Blair’s just wars’ that are widely discussed in the Russian language historical literature and press.